Good Guys with Guns : The Appeal and Consequences of Concealed Carry - Stroud, Angela (Book collections on Project MUSE., 2015)
"Today, more than 11 million Americans hold concealed handgun licenses, an increase from 4.5 million in 2007. Yet, despite increasing numbers of firearms and expanding opportunities for gun owners to carry concealed firearms in public places, we know little about the reasons for obtaining a concealed carry permit or what a publicly armed citizenry means for society. Angela Stroud draws on in-depth interviews with permit holders and on field observations at licensing courses to understand how social and cultural factors shape the practice of obtaining a permit to carry a concealed firearm"--